2013
DOI: 10.2214/ajr.12.8754
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT–Positive Internal Mammary Lymph Nodes: Pathologic Correlation by Ultrasound-Guided Fine-Needle Aspiration and Assessment of Associated Risk Factors

Abstract: Although fewer than 10% of breast cancer patients have positive IM nodes on (18)F-FDG PET/CT performed for initial staging or restaging, a positive IM node indicates a very high likelihood of malignant involvement on ultrasound-guided FNA. The presences of high tumor grade, LVI, or triple receptor-negative status are risk factors for IM node positivity on (18)F-FDG PET/CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 36 publications
3
25
0
Order By: Relevance
“…Wang et al showed that an fluorodeoxyglucose-avid IMLN in a breast cancer patient had a very high likelihood of malignancy, with 80% of the 25 patients who underwent fine-needle aspiration yielding positive results [19]. The mean size of the positive IMLNs was 8 mm, which falls within the size range of benign nodes in our study.…”
Section: Discussionsupporting
confidence: 75%
“…Wang et al showed that an fluorodeoxyglucose-avid IMLN in a breast cancer patient had a very high likelihood of malignancy, with 80% of the 25 patients who underwent fine-needle aspiration yielding positive results [19]. The mean size of the positive IMLNs was 8 mm, which falls within the size range of benign nodes in our study.…”
Section: Discussionsupporting
confidence: 75%
“…Previously reported prevalence of IMN adenopathy has ranged from 9.0% to 47.5% [6, 9, 20, 21], with the highest prevalence occurring in a group undergoing extended radical mastectomy [6]. The remainder of the patients received diagnoses by imaging.…”
Section: Discussionmentioning
confidence: 99%
“…However, that study considered only a small series of 8 patients, and biopsy was used to confirm the imaging findings in only 1 case. In a retrospective study by Wang et al, 15 110 of 1259 patients (9%) had PET/CT‐positive internal mammary LNs, and 25 patients underwent US‐guided fine‐needle aspiration for suspicious internal mammary LNs. Twenty of 25 patients (80%) had cytologically proven internal mammary LN metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Although ultrasound imaging (US), chest computed tomography (CT), magnetic resonance imaging, and [ 18 F]fluorodeoxyglucose (FDG) positron emission tomography (PET)/CT are used in breast imaging, the optimal imaging methods for detection of internal mammary LN metastases have not yet been established 5 14 . Several studies have reported the diagnostic performance of different imaging modalities for detection of these metastases; however, pathologic confirmation of metastases was lacking, with the exception of a small number of recently published studies 15 17 …”
mentioning
confidence: 99%